Effects of Vibration Located on the Steel Truss Bridges under Moving Load - Mohamad Ibrahim Zaed Ammar; Endah Wahyuni; Data Iranata (Institut Teknologi Sepuluh Nopember, 2017)
Structural vibration control as an advanced technology in engineering consists of implementing energy dissipation devices or control systems into structures to reduce excessive structural vibration, enhance human comfort and prevent catastrophic structural failure due to strong winds and earthquakes, among other inputs. When the bridge carries heavy traffic, vibrations in the bridge structural elements subjected to high levels of stress. This tension bridge subjected to fatigue. This paper studies and focus the effects of vibration of steel truss bridges and finally to suggest future directions of research and innovation. The possibilities of modal properties of global and local vibration method in determining the structural changes in the truss bridges discussed located to the results of finite element analysis.